A new role of supercritical ethanol in macroalgae liquefaction (Saccharina japonica): Understanding ethanol participation, yield, and energy efficiency. (1st January 2017) - Zeb, Hassan; Choi, Jaeyeon; Kim, Yunje; Kim, Jaehoon
Abstract: Liquefaction of macroalgae was performed in a stirred autoclave reactor using supercritical ethanol (scEtOH) as a solvent. There was a sharp transition in ethanol consumption during macroalgae liquefaction in scEtOH when the temperature was increased from 350 to 400 °C. At 350 °C, a small amount of ethanol (6 wt%) reacted with intermediates, while at 400 °C, 18 wt% of the ethanol was consumed. Taking into account this increased consumption of ethanol at 400 °C, the bio-oil yield decreased from 79.2 to 53.9 wt%, energy recovery from 202.5% to 72.2%, and energy efficiency from 111.6% to 62.7%. The produced bio-oil had a molecular weight of 398 g mol −1, a HHV of 36.49 MJ kg −1, an O/C ratio of 0.12, and a H/C ratio of 1.58. To confirm the unique role of scEtOH in biomass liquefaction, subcritical water (subH2 O) and supercritical water (scH2 O)-based liquefactions were carried out and the results compared with those obtained for scEtOH-based liquefaction. GC-MS results from the bio-oil produced with scH2 O revealed the percentage area of compounds containing an ethoxy group to be as low as 20%, while this value reached 62% when using scEtOH. Highlights: Supercritical ethanol not only acts as a solvent but also as a reagent. Ethanol consumption during reaction was calculated by GC-MS ethanol calibration. Bio-oil yield, ER and EE were re-calculated considering consumed amount of ethanol. Decrease in bio-oil yield, ER and EE when consumed ethanol was taken into account.